The Smoke Signals Radio Show Archive Project: An Introduction - Rothbauer, Paulette; Hadley, Amy; Harrington, Marni; Hill, Heather; Mendizabal, Serena; Pawlick-Potts, Danica; Smoke, Dan; Smoke, Mary Lou (KULA)

(untitled) (University of Victoria Libraries, 2021)
In this multimedia report we introduce our ongoing collaborative archival project to organize, describe, and provide access to digitized audio files from the long-running Indigenous radio broadcast called Smoke Signals, produced and hosted by Indigenous activists, community leaders, educators, and Elders Dan Smoke and Mary Lou Smoke.